Analytical analysis of the bifurcation behavior of creep groan. Issue 7 (18th March 2019) - Zhao, Xingwei; Gräbner, Nils; von Wagner, Utz; Hetzler, Hartmut
Abstract: Creep groan is one of the low frequency vibration phenomena, which can be observed in automotive disk brakes at low driving speeds [1]. In order to study fundamental mechanisms of creep groan, a model with bristle friction law was set up, for which the bifurcation behavior was studied numerically. A corresponding map reflecting regions with qualitatively different behavior was obtained and compared with experimental results [9–11]. In the work described in this paper, an analytical study based on an approach presented in [13, 14] is proposed as an alternative way to map the bifurcation behavior. The corresponding nonlinear model shows that the system may have three different parameter regions with different types of asymptotically stable solutions, i.e. an equilibrium solution, a stick‐slip limit cycle, and coexistence of them. The stick‐slip limit cycle can be interpreted as the origin of creep groan in a vehicle while the equilibrium solution is the desired non‐vibrating solution. As the regions reflect the risk of generation of creep groan, it can be used to evaluate the robustness of brake systems against creep groan. The analytical study is verified by experimental results. Abstract : Creep groan is one of the low frequency vibration phenomena, which can be observed in automotive disk brakes at low driving speeds [1]. In order to study fundamental mechanisms of creep groan, a model with bristle friction law was set up, for which the bifurcation behavior was studied numerically. A corresponding map reflecting regions with qualitatively different behavior was obtained and compared with experimental results [9–11]. In the work described in this paper, an analytical study based on an approach presented in [13, 14] is proposed as an alternative way to map the bifurcation behavior….